A cold dose of murder - George, Emily (Mystery writer) (George, Emily (Mystery writer). Cannabis café mystery., 2025)
"Chloe still can't believe the magic carpet ride her life has become. From a career-and-romantic crash-and-burn as a Parisian pastry chef, she turned things around by starting the Baked by Chloe cannabis café in her seaside hometown of Azalea Bay, California. Now one of the town's hottest spots, the café has earned a coveted booth in the Bay's famous summer ice cream festival and Chloe is excited to introduce her cannabis-infused flavors. Plus, a rave review by influential podcaster and food critic Calista Bryant is sending Chloe's sales into orbit--with no bad vibes in sight... Until Chloe finds Calista sprawled toes-up under an ice cream food truck--as dead as the Wicked Witch of the West. With so much already on her plate, Chloe is determined to avoid sleuthing this go-round. But when rival café owner and suspect Starr Bright asks Chloe to help prove she's innocent, she's soon hip-deep in the many enemies, competitors, and ex-friends the ruthlessly opinionated Calista was expert at racking up. And now Chloe is heading for what could be a life-ending buzz-kill--courtesy of one insidious murderer..."--